Sustainability Of The Forest Village Community Management Program In UPT KPHP Dolago Tanggunung - Kurniawan, Imam Wahid; Umar, Syukur; Naharuddin, Naharuddin (Mitra Sains, 2021)
The Indonesian government continously strives to increase the forest resources which continue be the problem is managing community around forests. It is due to weaknesses in management the forests area, to facilitate it is needed an institution that can manage the forest areas sustainability. Through KPH, forest management is getting better and sustainable. The aim of this research is to analyze the sustainability of the forest village community management program. This research was conducted for three months from june to August 2020 in Petimbe village and Sigimpu village, Palolo district, Sigi regency. The samples in this research were 58 respondens obtained by purposive sampling method. The data analysis method was descriptive analysis. The result shows that the sustainability of the forest village community management program obtains in to 3 dimensions (a) management planning dimension with the value of 180.89 in medium category, (b) The social community dimensions with the value of 197 in moderate category, (c) implementing management activities with the value of 127.6 in the low category